O fenômeno da despersonalização e suas relaões com a infra-humanização e o preconceito - Teixeira, Floricelia Santana (2014)
This paper approaches an insufficiently researched phenomenon in Social Psychology, depersonalization , which refers to the concept that there are humans who don´t trigger interest to the other , which are considered |non- individuals| as not equipped with a particular psychological dimension , making them invisible to the world . This paper starts from the hypothesis that through training tasks of impression, with the help of the Implicit Association Test ( IAT ) , we can obtain the speed of response in milliseconds during the evaluation of a target and thus suggest that when the respondent associates a concept with an attribute faster , easier and demonstrates a sense in this regard . The process of impression formation becomes more detailed and complex when more expenditure of time and attention in evaluating the target, occurring the target personalization. In this term, time is understood as the main indicator of personalization or depersonalization. The aim of our study I was to establish depersonalization and its relations with the infra - humanization, implicit prejudice , explicit prejudice through impression formation tasks with the aid of the IAT program. In the second study we are interested in the analysis of the impact of racial discrimination in access to health care, investigating the phenomenon of depersonalization as a trigger of misdiagnosis against black patients referred by the NHS or privately insured patients in medical care . Outcome of the study indicated that there were significant correlations between depersonalization and infra-humanization, r (49) = .32, p = .024 , in other words the individual who is depersonalized is infra-humanized as well . The depersonalization has not kept correlations with implicit prejudice, r (49 ) = . -12, P = .40, nor the explicit prejudice (49) = .07 , p = .65 . We don´t confirm our main hypotheses of the study II. However, even though it isn´t statistically significant, we found that mean values showed a more carefully analysis of the diagnostic evaluation to white patients of private agreement. As compared to the rate of misdiagnosis, the four conditions described by the patients in the videos, respondents erred least for white patients , regardless of being the SUS users or privately insured . We conclude the presence of implicit prejudice in both studies , confirming that negative stereotypes are still active , even if unconsciously on the attitudes of individuals so , and more that they don´t consciously perceive actions produce infra- humanization and depersonalized against blacks.